2019
DOI: 10.1002/lipd.12194
|View full text |Cite
|
Sign up to set email alerts
|

Niemann‐Pick C1‐like 1 Promotes Intestinal Absorption of Siphonaxanthin

Abstract: Siphonaxanthin is a carotenoid found in certain green algae, and its promising beneficial properties, such as its anti‐obesity effect, have recently been demonstrated. However, there is little information about the molecular mechanisms underlying intestinal absorption of siphonaxanthin. In this study, we aimed to elucidate how siphonaxanthin is transported across the intestinal epithelium using differentiated Caco‐2 cells (dCaco‐2 cells), recombinant proteins, and an animal model. Siphonaxanthin was taken up b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…For the other carotenoids (echinenone, alloxanthin, siphonaxanthin, and fucoxanthin), there is no evidence that the plasma concentration can reach 1.0 µM. However, using mice and differentiated Caco-2 cells, a well-investigated model of human intestinal epithelium, we previously showed that siphonaxanthin can be absorbed from the intestine to the same extent as β-carotene and lutein [19]. Comparative studies on the intestinal absorption of carotenoids would also be important for further understanding of the anti-inflammatory activities of carotenoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the other carotenoids (echinenone, alloxanthin, siphonaxanthin, and fucoxanthin), there is no evidence that the plasma concentration can reach 1.0 µM. However, using mice and differentiated Caco-2 cells, a well-investigated model of human intestinal epithelium, we previously showed that siphonaxanthin can be absorbed from the intestine to the same extent as β-carotene and lutein [19]. Comparative studies on the intestinal absorption of carotenoids would also be important for further understanding of the anti-inflammatory activities of carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Total lipids were extracted from the cells as described previously [19] and dissolved in 0.25 mL of methanol. After dilution with 0.75 mL of acetonitrile, 5 µL of each sample was analyzed using a Prominence HPLC system (Shimadzu, Kyoto, Japan) coupled to a QTRAP 5500 mass spectrometer (AB Sciex, Framingham, MA, USA).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…There are no reports on the detailed transport route of emulsified ubiquinone. On the other hand, it was reported that other emulsified fat-soluble micronutrients such as vitamin K, α-tocopherol and siphonaxanthin are transported by NPC1L1 [22,23,27]. Therefore, it is possible that CoQ10 is also transported by NPC1L1.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolyzed carotenoids (i.e., free carotenoids) are taken up by intestinal epithelial cells through both passive and facilitated diffusion pathways. Pharmacological inhibition studies suggest that scavenger receptor class B type 1 (SR-B1, encoded by SCARB1) and/or Nieman-Pick C1-like 1 (NPC1L1) are involved in facilitated diffusion of several carotenoids (8)(9)(10)(11)(12)(13). In addition, some genetic variants in SCARB1 and NPC1L1 have been reported to be associated with changes in serum concentrations of lutein and zeaxanthin, both of which are major dietary carotenoids and reported to be taken up partly through SR-B1-and NPC1L1-dependent pathways (14).…”
mentioning
confidence: 99%
“…1). The biological activities of siphonaxanthin have been extensively investigated (15)(16)(17)(18)(19), and we have previously shown that its intestinal absorption is facilitated by NPC1L1 (13). However, the biological activities and intestinal absorption mechanism of siphonein, a medium-chain fatty acid ester of siphonaxanthin, remain largely unknown.…”
mentioning
confidence: 99%